The Impact of Health Law Reforms on Patient Rights and Medical Professional Accountability Worldwide - Eryani, Susi; Samosir, Tony Richard Alexander; Sudaryat, Sudaryat (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2025)
This study examines the global impact of health law reforms on patient rights and the accountability of medical professionals through a qualitative methodology based on comprehensive library research and literature review. By analyzing legal frameworks, policy changes, and scholarly discussions from diverse international contexts, this research explores how recent reforms have shaped the protection of patient autonomy, informed consent, privacy, and access to quality healthcare. Additionally, the study investigates the evolving mechanisms of medical professional accountability, including regulatory oversight, disciplinary actions, and ethical standards. The literature reveals that health law reforms play a pivotal role in strengthening patient empowerment and ensuring that healthcare providers adhere to heightened standards of professional conduct. While the reforms have led to improved transparency and patient-centered care in many regions, challenges persist related to enforcement disparities, cultural differences, and resource limitations. Moreover, the study highlights the tension between protecting patient rights and supporting medical professionals in clinical decision-making, emphasizing the need for balanced legal frameworks. This qualitative synthesis provides insights into the effectiveness of various reform strategies, underscoring the importance of harmonizing legal provisions with healthcare realities. The findings contribute to policy discourse by identifying best practices and gaps in implementation that influence both patient outcomes and medical accountability. This research offers valuable guidance for lawmakers, healthcare administrators, and advocates aiming to enhance the legal foundations of health systems worldwide. Future research is encouraged to conduct empirical evaluations of reform impacts at national and local levels to deepen understanding of their practical implications.